2015
DOI: 10.3233/ppr-150067
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the relationship between thermal imaging and digital thermometer testing at the knee

Abstract: U n c o r r e c t e d A u t h o r P r o o f BACKGROUND:A number of research papers and theoretical clinical models summarising how temperature of the skin over the knee may be altered according to different pathological processes have been published. Thermal imaging (TI) is generally regarded as the 'Gold' or 'reference' standard for measuring skin temperature, however this technology is not widely accessible to most musculoskeletal physiotherapists working in clinical environments. This is largely due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The healthy volunteer study (normative dataset) recruited 71 participants without back or lower limb problems and without a history of knee surgery. This healthy volunteer study was a validation study of the digital thermometer used in all three PFP studies against thermal imaging measurements, and its methods are reported in detail in Erande et al [28].…”
Section: Description Of Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…The healthy volunteer study (normative dataset) recruited 71 participants without back or lower limb problems and without a history of knee surgery. This healthy volunteer study was a validation study of the digital thermometer used in all three PFP studies against thermal imaging measurements, and its methods are reported in detail in Erande et al [28].…”
Section: Description Of Datasetsmentioning
confidence: 99%
“…Of the three studies undertaken in newly diagnosed PFP patients, two were undertaken in the United Kingdom (UK): London [28] and the UK wide TIPPs (Targeted Interventions for Patellofemoral Pain study) [15], and one in Turkey [29]. All three studies used the same participant eligibility criteria used in previous studies [30,31].…”
Section: Description Of Datasetsmentioning
confidence: 99%
See 2 more Smart Citations